The quest for more and more education: Implications for social mobility - Joanne Lindley; Stephen Machin (Institute for the Study of Labor (IZA), 2012)
In this paper, we discuss the quest for more and more education and its implications for social mobility. We document very rapid educational upgrading in Britain over the last thirty years or so and show that this rise has featured faster increases in education acquisition by people from relatively rich family backgrounds. At the same time, wage differentials for the more educated have risen. Putting these two together (more education for people from richer backgrounds and an increase in the payoff to this education) implies increasing within generation inequality and, by reinforcing already existent inequalities from the previous generation, this has hindered social mobility. We also highlight three important aspects that to date have not been well integrated into the social mobility literature: the acquisition of postgraduate qualifications; gender differences; and the poor education performance of men at the lower end of the education distribution.
Keywords: J24; J31; 330; education; wages; inequality; social mobility; Bildungsverhalten; Soziale Schicht; Lohnstruktur; Hochqualifizierte Arbeitskräfte; Soziale Ungleichheit; Soziale Mobilität; Schätzung; Großbritannien